2021
DOI: 10.3389/fcimb.2021.641261
|View full text |Cite
|
Sign up to set email alerts
|

Common Dysregulation of Innate Immunity Pathways in Human Primary Astrocytes Infected With Chikungunya, Mayaro, Oropouche, and Zika Viruses

Abstract: Arboviruses pose a major threat throughout the world and represent a great burden in tropical countries of South America. Although generally associated with moderate febrile illness, in more severe cases they can lead to neurological outcomes, such as encephalitis, Guillain-Barré syndrome, and Congenital Syndromes. In this context astrocytes play a central role in production of inflammatory cytokines, regulation of extracellular matrix, and control of glutamate driven neurotoxicity in the central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 119 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…Previous reports revealed that numerous viral infections modify the host transcriptome, including both coding and non-coding transcripts [5][6][7][8]; moreover, lncRNAs induced by infection may influence viral pathogenesis and replication (as reviewed by Fortes and Morris (2016) [25]). Although intense research is being done on CHIKV infection and pathogenesis, the mechanisms mediating host-virus interactions are still elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports revealed that numerous viral infections modify the host transcriptome, including both coding and non-coding transcripts [5][6][7][8]; moreover, lncRNAs induced by infection may influence viral pathogenesis and replication (as reviewed by Fortes and Morris (2016) [25]). Although intense research is being done on CHIKV infection and pathogenesis, the mechanisms mediating host-virus interactions are still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the dynamics of host-pathogen interaction can help the search for potential therapeutic targets. Several reports evidence that viral infections significantly alter host transcriptome, including CHIKV [5][6][7]. These changes may be related to transcriptional and posttranscriptional control mechanisms mediated by long non-coding RNAs (lncRNAs) in several ways [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle arrest might account for the increased availability of capped mRNAs to act as donors for translation, the cap-snatching mechanism [ 163 , 164 ]. The down-regulation of interferon response and genes with antiviral activities was also observed (RSAD2—Viperin; OASL and OAS1—2′5′-Oligoadenylate Synthethase, MX1/2—MX Dynamin-like GTPase 1; IFIT2—Interferon-induced Protein with Tetratricopeptide Repeats 2), and evidence of the down-modulation of ion channels, transmembrane solute carriers and synapse regulation pathways was also identified, revealing manifestations of OROV neuropathology [ 165 ].…”
Section: Omic’s Study Across Members Of Bunyavirales Order— ...mentioning
confidence: 99%
“…Arbovirus-caused meningitis is also frequently associated with severe neurological outcomes. The comprehensive genome-wide transcriptome analysis of human primary astrocytes infected with Chikungunya, Mayaro, Oropouche, and Zika viruses described by Viana Geddes et al, has revealed a common pattern in downregulation of the host innate immune response, antiviral response, and expression levels of inflammatory cytokines associated with interferon stimulation for all the arboviruses tested (Viana Geddes et al, 2021). These findings point towards a co-evolution that all these arboviruses have engaged in developing mechanisms to escape the antiviral response induced by interferon (IFN) (Viana Geddes et al, 2021).…”
Section: Viral Meningitismentioning
confidence: 99%